Kepastian Hukum Dokumen Elektronik dalam Perkara Perceraian Melalui Sistem E-Court di Pengadilan Agama Barru - Risdawati Risdawati; Hannani; Budiman (Jurnal Hukum Lex Generalis, 2026)
This study examines the legal certainty of using electronic documents as evidence in divorce cases through the e-court system at the Barru Religious Court. The research problem lies in the lack of uniformity in the verification process, assessment of authenticity, and evidentiary value of electronic documents submitted by the parties. In divorce cases, electronic documents such as claims, responses, chat records, and other digital files are increasingly used in court proceedings. If this issue remains unresolved, it may lead to legal uncertainty, differences in judges’ assessments, and potential prejudice to the parties in proving their claims. Normatively, the use of electronic documents has a clear legal basis, particularly Article 5 paragraph (1) of the Law on Electronic Information and Transactions, which states that electronic documents and/or their printouts constitute valid legal evidence, as well as Supreme Court Regulation Number 1 of 2019 concerning Electronic Case Administration and Trial Proceedings in Court. This study employs an empirical method with a field approach. Data were collected through interviews, observation, and documentation at the Barru Religious Court. The results show that electronic documents have been used in e-court practice, but they have not fully provided legal certainty. The main obstacles include doubts regarding document authenticity, the potential for data manipulation, limited digital literacy, and the absence of uniform parameters in judges’ assessment. Therefore, clearer verification standards and improved digital competence of court officials are needed.